A Natural Rubber Waste Derived Surfactant for High Internal Phase Emulsion Templating of Poly(Dicyclopentadiene). Issue 14 (13th May 2021) - Schallert, Viktor; Slugovc, Christian
Abstract: The use of a surfactant derived from the degradation of natural rubber gloves via cross‐metathesis with methyl acrylate and subsequent saponification of the ester group for the stabilization of water in dicyclopentadiene high internal phase emulsions is described. The versatility of the resulting high internal phase emulsion is demonstrated by polymerizing the continuous dicyclopentadiene phase via ring‐opening metathesis polymerization yielding macroporous poly(dicyclopentadiene) foams with a porosity of 82%. The use of the ionic surfactant allows for the preparation of foams, which are resistant to absorb water. This property is hitherto not accessible with protocols involving the use of nonionic surfactants commonly employed in emulsion templating of polymers. Abstract : An anionic surfactant derived from the degradation of natural rubber waste via cross‐metathesis with acrylates and subsequent saponification is used for stabilizing high internal phase emulsions of water in dicyclopentadiene. Subsequent curing of the continuous phase by ring‐opening metathesis polymerization (ROMP) demonstrates the utility of these emulsions for the preparation of macroporous polymer foams.